2020
DOI: 10.3390/molecules25061312
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Tetracycline in Sewage and Dairy Products with High-Stable MOF

Abstract: Serious environmental and human health problems caused by the abuse of antibiotics have attracted worldwide concern. Recently, metal–organic frameworks (MOFs) with high porosity have drawn wide attention for their effects in the adsorption and removal of pollutants from complex matrices. Herein, a high-stable metal organic framework (MOF), i.e., ((ZnCl2)3(L)2·DMF)n, where L=1,3,5-tris((pyridin-4-ylthio)methyl)benzene), MOF 1, was applied to adsorb and remove tetracycline from sewage and dairy products. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The kinetic experimental data were treated using the first-order (Equation (10)), second-order (Equation (11)) and intraparticle diffusion models (Equation (12)) [ 56 ], respectively. Furthermore, typical isothermal experiments were performed using a group of Pb(II) solutions with different initial concentration at 30, 40, and 50 °C respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The kinetic experimental data were treated using the first-order (Equation (10)), second-order (Equation (11)) and intraparticle diffusion models (Equation (12)) [ 56 ], respectively. Furthermore, typical isothermal experiments were performed using a group of Pb(II) solutions with different initial concentration at 30, 40, and 50 °C respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of contact time, dosage, and pH were examined for two categories of experiments. The contact time was 20-180 min, the dosage was 5-40 mg, and the initial pH (3)(4)(5)(6)(7)(8)(9)(10)(11) was adjusted with 0.1 mM HCl or 0.1 mM NaOH. For the adsorption performance of Fe 3 O 4 @ZIF-8@ZIF-67, the initial concentration of TC (20-160 mg L − 1 ), the adsorption temperature (25-45℃), humic acid concentration (0-8 mg L − 1 ), and other adsorbents (activated carbon (AC), Fe 3 O 4 @ZIF-8, and nanometer zero-valent iron (nZVI)) were discussed.…”
Section: Batch Experimentsmentioning
confidence: 99%
“…The past three decades have witnessed an enormous growth in MOF research from synthesis to uses in adsorption, storage, separation and catalysis (Stock and Biswas, 2012). Numerous previous studies have shown that MOFs have an excellent effect on TC removal from wastewater with their large surface areas and high porosity (Li et al, 2020;Xiao et al, 2020). To date, most studies have focused on the use of MOFs as an adsorbent and little information is available on the performance and mechanism of TC removal from wastewater via synergetic adsorption and Fenton-like oxidation using magnetic-MOFs.…”
mentioning
confidence: 99%
“…Stock TC solution (Sigma), 250 mg L −1 , was prepared with deionised water. For the biosorption experiments, TC solutions of different concentrations (25,50,75 and 100 mg L −1 ) were prepared by adequate dilution of the stock solution with deionized water. All solutions were prepared daily.…”
Section: Reagents and Equipmentmentioning
confidence: 99%
“…An attractive alternative to the methods listed above is adsorption, due to its simplicity, safety, economic feasibility, and removal efficiency at low sorbent concentrations. A wide variety of adsorbents have been studied for tetracyclines removal from aqueous solutions: carbon-based materials (biochar, activated carbon, carbon nanotubes, graphene) [16], silica [17], pumice stone [18], biopolymers (chitosan and modified alginate) [19,20], algae [21,22], metal-organic frameworks -MOFs [23][24][25], magnetic nanocomposites [26][27][28].…”
Section: Introductionmentioning
confidence: 99%